Réponses

2014-04-18T14:06:38+02:00
A= 7(x-3)²+2x(5x-15)
= 7(x²-9)+10x²-30x
7x²-63+10x²-30x
=17x²-30x-63

B= (x+5)²-(x-13)(2x+1)
x²-5x+5x-25-(2x²+x-26x-13)
=x²-5x+5x-25-2x²-x+26+13
=x²-x+14

C=(5x+4)(5x-4)+(3x-4)²
5x²-4²+9x²+12-12x-16
=14x²+12x-20

D je pense qu'il manque un signe au début entre le 3 et le 7

E=(7x+9)²+(2x-1)(2-5x)
49x²-63x+63x-81+4x-10x²-2+5x
=39x²+9x-83
Effectivement c'est (3x-7) ^^' MERCI
ok donc 8(3x²-7x-3x-7)-x²+3x 24x²-56x-24x-56-x²+3x 23x²-77x-56
Thank's ;)
  • Utilisateur Brainly
2014-04-18T14:29:28+02:00
A= 7(x-3)²+2x(5x-15)
= 7(x²-9)+10x²-30x
7x²-63+10x²-30x
=17x²-30x-63

B= (x+5)²-(x-13)(2x+1)
x²-5x+5x-25-(2x²+x-26x-13)
=x²-5x+5x-25-2x²-x+26+13
=x²-x+14

C=(5x+4)(5x-4)+(3x-4)²
5x²-4²+9x²+12-12x-16
=14x²+12x-20

D=8(3x²-7x-3x-7)-x²
3x 24x²-56x-24x-56-x²
3x 23x²-77x-56


E=(7x+9)²+(2x-1)(2-5x)
49x²-63x+63x-81+4x-10x²-2+5x
=39x²+9x-83